Cycle time optimization of semiconductor wafer fabrication system using simulation - Kyaw, Soe Nyunt. (2008)
Focuses mainly on batch size decision policies as part of cycle time optimization techniques. A simplified semiconductor wafer fabrication system model is built by using a simulation tool, ProModel. Then a particular product type is selected to run the simulation model.